2013
DOI: 10.2478/s11696-012-0295-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lentil and bean flours on rheological and baking properties of wheat dough

Abstract: The potential of legume flours (lentil and bean) in bakery applications was investigated. The study indicated that legume flours were characterised by high protein (27.30–27.35 mass %) and total dietary fibre (14.91–21.52 mass %), relatively high water holding capacity (4.71–5.42 g g−1), and good emulsifying properties (emulsifying capacity: 32.73–46.96 cm3 per 100 cm3 and emulsion stability: 60.52–90.90 cm3 per 100 cm3). Fine wheat flour was partially substituted with 10 mass %, 20 mass %, and 30 mass % level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 39 publications
6
54
0
1
Order By: Relevance
“…In addition, the composite flours with more chickpea flour substitution showed larger farinograph water absorption values and longer dough development times (DDT) as compared to 100% wheat flour control. Similar results have been demonstrated by other researchers when pulse flours were used to substitute wheat flour at different proportions (Hallén, İbanoğlu, & Ainsworth, ; Kohajdová, Karovičová, & Magala, ). However, discrepancies have also been shown in the literature: Portman et al () found decreased farinograph water absorption and DDT when using 5%, 10%, 15%, 20%, and 40% lentil flour to replace wheat flour in bread formula; Ficco et al () observed no significant changes in farinograph water absorption and DDT (except an increase in DDT at 30% level) after replacing wheat flour with 10%, 15%, 20%, and 30% yellow pea flour.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, the composite flours with more chickpea flour substitution showed larger farinograph water absorption values and longer dough development times (DDT) as compared to 100% wheat flour control. Similar results have been demonstrated by other researchers when pulse flours were used to substitute wheat flour at different proportions (Hallén, İbanoğlu, & Ainsworth, ; Kohajdová, Karovičová, & Magala, ). However, discrepancies have also been shown in the literature: Portman et al () found decreased farinograph water absorption and DDT when using 5%, 10%, 15%, 20%, and 40% lentil flour to replace wheat flour in bread formula; Ficco et al () observed no significant changes in farinograph water absorption and DDT (except an increase in DDT at 30% level) after replacing wheat flour with 10%, 15%, 20%, and 30% yellow pea flour.…”
Section: Introductionsupporting
confidence: 90%
“…This particular chemical composition was associated with a reduction in incidence of colon cancer and type‐2 diabetes, but also with a reduction in cholesterol and lipid effects in human (Agriculture and Agri‐Food Canada, , ). Unfortunately, nowadays the consumption of legumes is in decline because dietary habits have changed; therefore, the food industry is looking for new ways to use legumes and the creation of new functional foods (Kohajdová et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Common beans have received increased attention because of their beneficial physiological effects in reducing cardiometabolic risk factors and a broad range of chronic diseases (Hayat, Ahmad, Masud, Ahmed, & Bashir, 2014). Dry beans are the staple food of many countries in America and Asia; however, despite their nutritional value and beneficial effects common beans are largely underexploited and their worldwide consumption is declining (Kohajdová, Karovič ová, & Magala, 2013). In this context, one valuable approach to enhance common bean intake and uses is their application in the design of novel and healthy foods.…”
Section: Introductionmentioning
confidence: 99%